How to Strengthen Patients’ Meaning Response by an Ethical Informed Consent in Psychotherapy - Trachsel, Manuel; grosse Holtforth, Martin (Frontiers in Psychology, 2019)
In the present contribution, we argue that all health care professionals and particularly psychotherapists should provide a plausible rationale for their treatment including an etiological model and a model of unique and common change mechanisms. The provision of a plausible rationale has two goals: (1) meet the ethical challenge of informed consent, and (2) to improve treatment outcome by fostering the meaning response. In the course of the ethical and a legal obligation of psychotherapists to obtain patients’ informed consent before initiating psychotherapy, patients have the right to receive maximally comprehensive information for providing their consent, which - among other information about the treatment (such as general psychotherapeutic approach, setting, and procedures) – should include a plausible treatment rationale. A useful concept in conceptualizing and communicating a treatment rationale as part of the informed consent procedure is Moerman’s general notion of the meaning response as the physiological or psychological effects of meaning in the course and treatment of an illness. The more compelling the rational explanation of the targeted treatment effects, the stronger the meaning response is expected to be. As the mechanisms of change in psychotherapy are known to be quite abstract and considered common to all approaches to a large extent, it seems especially important to provide a convincing treatment rationale to strengthen trust in the therapist and potentially foster positive expectations of process and outcome. To that extent, strengthening a patient`s meaning response to information provided at the beginning of psychotherapy may be central to activating common therapeutic factors.